Role of epigenetic factors in the development of mental illness throughout life. (January 2016) - Guintivano, Jerry; Kaminsky, Zachary A.
Highlights: Specific developmental windows are linked with higher risk for psychiatric disease. Psychiatric diseases show a range of heritabilities and are linked to environmental exposures. Epigenetics may mediate the environmental effects on existing genetic burden. DNA methylation change during sensitive periods may result in psychiatric phenotypes. Environment-induced epimutations may be seen across tissues and used as biomarkers. Abstract: Psychiatric disease is believed to result from a combination of genetic vulnerability and environmental influence. At the crux are epigenetic modifications, which mediate the influence of environment on the genome. Twin and genome-wide association studies demonstrate a wide range of heritabilities across psychiatric disorders, while epidemiological and animal models implicate distinct developmental windows where environmental factors may interact with genetic vulnerability to confer risk. Certain developmental periods appear to be more prone to these influences including during gestation, in the early postnatal period, and during periods of major hormonal rearrangement. Here we review the role of environmental factors capable of epigenetic reprogramming during these periods and present evidence for the link between these modifications and disease. The cross tissue relevance of environmentally induced epigenetic change and its utility for identifying peripheral biomarkers is discussed.